Լեզվամշակութային համադրությունների սահմանները - Արսեն Բոբոխյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В течение последних 200 лет, в поисках сложной проблемы интерпретации языковых единиц, специалисты часто обращаются к данным материальной культуры или наоборот. В целом, в этом направлении точки зрения развивались путем “из обьекта к контексту”. During the last 200 years, in search of the difficult problem of interpretation of language units, specialists often turn to the data of material culture or vice versa. In general, the viewpoints in this direction developed “from the subject to the context”.
Keywords: Language and Literature